Step (i) Divide each side by *a* which is 4 (so that the coefficient of the *x*^{2} is 1)

`x^2+x/4=3/4`

Step (ii) Rewrite the equation with the constant term (ie. '*c*') on the right side.

[No need in this example]

Step (iii) Complete the square by adding the square of one-half of the coefficient of *x* to both sides, that is `(b/2)^2`.

`x^2+x/4+(1/8)^2=3/4+(1/8)^2`

`x^2+x/4+1/64=3/4+1/64`

Step (iv) Write the left side as a square and simplify the right side.

`(x+1/8)^2=(48+1)/64=49/64`

Step (v) Equate and solve

`x+1/8=+-sqrt(49/64)=+-7/8`

So

`x=-1/8+7/8=3/4`

or

`x=-1/8-7/8=-1`

This gives `x=3/4` or `x=-1`.

Get the Daily Math Tweet!

IntMath on Twitter